Sosialisasi SAJAG (Serbuk Ajaib Penjernih Air Gambut) Untuk Pembentukan Usaha Mikro Kecil (UMK) Mahasiswa Universitas Riau - Budijono, Budijono; Harjoyudanto, Yudho; Sibagariang, Rina D’rita; Kamaruddin, Eddiwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Empowerment for Riau University students and graduates who already own small enterprises (UMK) or who do not yet own them can help a country's economy by boosting its overall prosperity. The location of service activities with this entrepreneurship development scheme in 2022 is on Jl. Merak Sakti Gang Hijrah Panam Pekanbaru City. The method of implementing community service activities with the Entrepreneurship Development Program Scheme is carried out in the form of socialization. The target of community service activities with the entrepreneurship development scheme was the general public, 25 students of the Faculty of Fisheries and Maritime Affairs, University of Riau (UNRI). In this activity, pre-test and post-test were carried out to see the achievement of activities. After the implementation of this activity, it was found that the service activities with this entrepreneurship scheme had been carried out with the target group of 25 alumni and students of the University of Riau with a level of knowledge and understanding reaching 97%. The activity concludes that SAJAG production is feasible to be carried out as Micro Small Business Empowerment (UMK).